Nitrogen Distribution in Annual Growth of ‘Italia’ Table Grape Vines - Ferrara, Giuseppe; Malerba, Anna Daniela; Matarrese, Angela Maria Stella; Mondelli, Donato; Mazzeo, Andrea (Frontiers in Plant Science, 2018)
Little information is available about nitrogen (N) content and its concentration in table grape vines. Knowledge of the quantity of N accumulated by the vine organs during the season could support sustainable fertilization programs for table grape vineyards. The aim of the present study was to determine the N content and its concentration in different annual organs, including summer and winter pruning materials, clusters at harvest, and fallen leaves at post-harvest. Specifically, biomass and N were analyzed at six phenological growth stages (flowering, berry-set, berry growth, veraison, ripening, and harvest) from 2012 to 2015. Nitrogen concentration was highest (>40 g/kg d.w.) in the leaves of the secondary shoots at flowering, whereas values >30 g/kg were measured in the leaves of the primary shoots. Nitrogen concentration in the clusters at harvest was 5.3–7.6 g/kg with an accumulation of 18.6–25.4 g/vine in the seasons. The decrease of N content in the primary leaves after flowering indicated a remobilization toward the clusters, which acted as a stronger sink. Later in the season (veraison-ripening), leaves translocated N to permanent organs and primary stems. Pruned wood and fallen leaves accounted for the largest N removal from the vine after clusters, 6.0–7.9 and 9.2–10.2 g/vine, respectively. With regard of the vine annual biomass, the growth followed a sigmoidal model reaching 7300–7500 g of d.w./vine at harvest. Vine leaf area, including both primary and secondary leaves, peaked at veraison (17–21 m2). Vines accumulated ≅35 g/vine of N at harvest, not considering the N removed with the intense summer pruning practices (≅7 g/vine) and the fraction mobilized toward the storage organs (10–15 g/vine). The overall N required by the vine was around 50–55 g/vine, which corresponded to ≅80 kg of N/ha in a vineyard with 1500 vines and a yield of 40 t/ha. Summer and winter pruning practices removed 29–31 g/vine of N which will be partly available (to be considered in the fertilization schedule) for the vine in the successive years if pruned residues were incorporated and mineralized in the soil.